2016
DOI: 10.1111/jace.14211
|View full text |Cite
|
Sign up to set email alerts
|

Domain Structure and Enhanced Electrical Properties in Sodium Bismuth Titanate Ceramics Sintered from Crystals with Different Morphologies

Abstract: Sodium bismuth titanate (Na 0.5 Bi 0.5 TiO 3 , NBT) crystals with different morphology, wires, plates and cubes, were synthesized by hydrothermal method. The domain structure in as-synthesized poled NBT ceramics was observed. The results demonstrate that the domain width of the poled NBT ceramics sintered from wire crystals is slightly larger than that of the NBT ceramics sintered from cube crystals, while the NBT ceramics sintered from plate crystals possess the largest domain width. In particular, the poled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Various mechanisms for the evolution of nanocubes and nanobers have been proposed, including dissolution-recrystallization and oriented growth. 9 In the case of low NaOH concentration, the growth rate is different in different directions producing plates and agglomerations. The increase of mineralizer concentration might hasten the kinetics of dissolution-recrystallization process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Various mechanisms for the evolution of nanocubes and nanobers have been proposed, including dissolution-recrystallization and oriented growth. 9 In the case of low NaOH concentration, the growth rate is different in different directions producing plates and agglomerations. The increase of mineralizer concentration might hasten the kinetics of dissolution-recrystallization process.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, sintered BNT nanocubes have higher mechanical quality factor (Q m ) than that of nano-ber counterparts. 9 It is also reported that crystal morphology of the BNT nanostructures, as a template, controls the grain growth and density of ceramics. Ceramics sintered from BNT nanobers have a large grain size which facilitates domain switching and subsequently results in a signicant improvement of piezoelectric and ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,10] Due to the high temperature in calcination for getting pure crystallized PbTiO 3 perovskite, severe Pb loss and agglomeration always occur accompanying the formation of PbTiO 3 perovskite. [7,8,[19][20][21][22][23] Generally, under the effect of strong bases, such as potassium hydroxide and sodium hydroxide, PbTiO 3 perovskite cubic or tetragonal particles are obtained by hydrothermal reaction route. Among these methods, the hydrothermal technique is an aqueous-based precipitation route, which could control over the nucleation and crystal growth by tuning the hydrothermal reaction conditions, such as hydrothermal treatment temperature, time, starting precursors, mineralizer, feedstock concentration, as well as modifiers.…”
Section: Introductionmentioning
confidence: 99%